Antagonistic potential of native agrocin-producing non-pathogenic Agrobacterium tumefaciens strain UHFBA-218 to control crown gall in peach - Sharma, Aditi; Gupta, A.; Khosla, K.; Mahajan, Rishi

(untitled) - Mahajan, P. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2017)
A non-pathogenic agrocin-producing native isolate of Agrobacterium tumefaciens strain UHFBA-218 was tested as a biological control agent against the peach crown gall. This strain was compatible with all the recommended pesticides used in stone fruits in the integrated pest management (IPM) module, except for copper oxychloride, which was detrimental to its growth. Upon artificial co-inoculation of 4-wk-old plants of tomato var. Solan Gola with A. tumefaciens strain UHFBA-218 and tumorigenic A. tumefaciens strain Peach 2E-10, out of the 27 isolates recovered, six were transconjugants showing selective acquisition of tumorigenic factors as made evident by amplification with ipt and virD2 primers, whereas the rest of the isolates did not acquire any of these tumorigenic factors. A white stone powder-based formulation of this isolate (103.3 × 108 cfu g-1) retained appreciable viability for up to 6 months at room temperature. When peach roots and seeds were soaked in cell suspensions of different doses of a white stone powder-based bioformulation of UHFBA-218 before planting in the field, the number of plants with tumours was reduced, with the lowest incidence of crown gall being observed in the 0.1% UHFBA-218 root dip treatment, i.e. 1.48% and 0.80% during the years 2013 and 2014, respectively. No incidence of crown gall was observed in the three seed dip treatments, i.e. 30-min dip in UHFBA-218 followed by 1 h of shade drying, stratified seeds dipped for 30 min in 0.1% suspensions of strains UHFBA-218 or K84 followed by 1 h of shade drying before sowing, as compared with 14.76% incidence in untreated plants.